2018
DOI: 10.1159/000495007
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Stress During Pregnancy Is Associated with Decreased Cortisol and Cortisone Levels in Neonatal Hair

Abstract: Background: Hair glucocorticoids (GCs) offer a retrospective view on chronic GC exposure. We assessed whether maternal pre- and postnatal stress was associated with neonatal and maternal hair GCs postpartum (pp). Methods: On the first day pp 172 mother-infant pairs donated hair, of whom 67 had consulted a centre of expertise for psychiatric disorders during pregnancy. Maternal stress was scored on the Hospital Anxiety and Depression Scale during the first/second (n = 46), third trimester (n = 57), and pp (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 48 publications
2
13
1
1
Order By: Relevance
“…17 Studies evaluating the effects of stress and psychopathology on maternal and foetal HCC during pregnancy and beyond are rapidly emerging, but results are inconclusive. [32][33][34][35][36][37][38] This might be partly explained by differences in study sample (i.e. healthy versus depressed mothers) and different definitions of 'stress' (i.e.…”
Section: Hpa Axis and Psychiatric Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Studies evaluating the effects of stress and psychopathology on maternal and foetal HCC during pregnancy and beyond are rapidly emerging, but results are inconclusive. [32][33][34][35][36][37][38] This might be partly explained by differences in study sample (i.e. healthy versus depressed mothers) and different definitions of 'stress' (i.e.…”
Section: Hpa Axis and Psychiatric Disordersmentioning
confidence: 99%
“…Inconsistent results have emerged on the association between maternal prenatal cortisol levels and self-reports of prenatal psychological distress, elevated symptoms of prenatal depression, anxiety and antidepressant use. Evidence in different studies does show that excess maternal cortisol during pregnancy is associated with decreased infant cortisol levels, as measured in infant hair, shortly after birth 33 , 39 and at 12 months’ postpartum. 34 In 2-year-old children, Bryson et al 40 found a significant association between maternal and infant HCC that was not mediated by measures of early childhood adversity.…”
Section: Maternal Hpa Axis Functioning and Its Influence On The Foetusmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrastingly, van der Voorn et al (2018) 49 found a significant association between prenatal maternal anxiety and decreased glucocorticoid levels in neonatal hair. Hair samples were, however, taken just one day postpartum, at which point they would be representative of prenatal, and not postnatal, HPA activity.…”
Section: Effects On Offspring Hpa Activitymentioning
confidence: 89%
“…Three recent studies addressed this issue in human neonates. First, Van der Voorn et al (2018) measured hair CORT and cortisone in hair samples collected from a sample of Dutch mother‐infant dyads on the first day postpartum. The full length of infant hair was analyzed, as was the first centimeter proximal to scalp (representing roughly the previous month of hormone accumulation) in the mothers.…”
Section: Prenatal Stress and Cortisol Measurement In Hair And Nailsmentioning
confidence: 99%